2013
DOI: 10.1080/07373937.2013.783593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Whey Protein Isolate on Spray-Drying Behavior of Honey with Maltodextrin as a Carrier Material

Abstract: The efficiency of two drying carriers, namely whey protein isolate (WPI) and maltodextrin (MD), alone or in combination, was evaluated during spray-drying of honey. No powder was recovered when pure honey was spray-dried. Honey powders were successfully obtained (powder recovery >50%) by adding MD and WPI alone at a Honey: MD ratio of 40:60 or at a Honey:WPI ratio of 70:30. The addition of a small amount of WPI (as low as 0.5% w/w) to MD reduced the amount of carriers required to spray-dry honey. Powder recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
116
7
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 41 publications
14
116
7
2
Order By: Relevance
“…It is also generally recognized that dispersions of maltodextrin and gum Arabic are Newtonian in nature at concentrations of >10% [Meer, 1980;Dokic et al, 1998;Mothe & Rao, 1999]. In the work presented by Shi et al [2013], an increase in MD total solid ratio in the feed solution (water/MD/Capilano Natural Australian Unauthenticated Download Date | 5/10/18 9:11 PM honey solution) from 0 to 39.5% led to a negligible increase in viscosity from 6.00 to 8.00 mPa×s.…”
Section: Viscositymentioning
confidence: 96%
“…It is also generally recognized that dispersions of maltodextrin and gum Arabic are Newtonian in nature at concentrations of >10% [Meer, 1980;Dokic et al, 1998;Mothe & Rao, 1999]. In the work presented by Shi et al [2013], an increase in MD total solid ratio in the feed solution (water/MD/Capilano Natural Australian Unauthenticated Download Date | 5/10/18 9:11 PM honey solution) from 0 to 39.5% led to a negligible increase in viscosity from 6.00 to 8.00 mPa×s.…”
Section: Viscositymentioning
confidence: 96%
“…Shi et al . () studied the efficiency of whey protein isolate (WPI) and maltodextrin as drying aids during honey spray drying. The addition of small amount of WPI (0.5% w/w) reduced the amount of carrier required to spray‐dry honey.…”
Section: Introductionmentioning
confidence: 91%
“…During spray drying (outlet air temperature ranging from 60 to 100 °C), usually the product temperature exceeds the T g . As a result, the problems of stickiness are observed – material in an amorphous ‘rubbery’ form is not transformed into a powder form, due to particle–particle cohesion and particle–wall adhesion the liquid‐like material sticks to the chamber walls (Truong et al ., ; Shi et al ., ). There are several approaches to eliminate these stickiness problems: (i) the selection of appropriate process parameters, (ii) the use of specially constructed dryers, (iii) the addition carrier substances and drying aids.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Saavedra et al (2015) reported the T g in the range of 52-100°C of a set of MXs with different DE and DP (Saavedra et al, 2015). Overall, for the drying of fruit juices it is preferred to employ a carrying agent with a T g higher than 100°C and in a composition relative to the food product of 10-60% in weight (Mishra, Mishra, & Lata, 2014;Oberoi & Sogi, 2015;Shi, Fang, & Bhandari, 2013). It is worth to mention that in the case of multicomponent systems, the overall T g of the system does not follow an additive behavior of the individual components, and additionally it depends on the amount of water adsorbed from the environment.…”
Section: Setting the Spray Drying Conditions Based On The T G Of The mentioning
confidence: 99%